1993
DOI: 10.1002/ccd.1810300309
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis and pulmonary embolism following cardiac catheterization

Abstract: We report 4 cases of deep venous thrombosis and/or pulmonary embolism after diagnostic cardiac catheterization. Two of these cases followed left heart catheterization alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Larger hematomas, however, have been associated with formation of deep vein thrombosis and nerve compression resulting in sensory loss. ( Butler & Webster, 2002 ; Shammas, Reeves, & Mehta, 1993 ) Large hematomas requiring blood transfusion occurred in 2.8% of the population in a large single center registry from 2000-2005 ( Table 2 ). ( Doyle et al , 2008 ) Manual compression of the proximal femoral artery and hematoma immediately following discovery and examination should be initiated.…”
Section: Local Vascular Injurymentioning
confidence: 99%
“…Larger hematomas, however, have been associated with formation of deep vein thrombosis and nerve compression resulting in sensory loss. ( Butler & Webster, 2002 ; Shammas, Reeves, & Mehta, 1993 ) Large hematomas requiring blood transfusion occurred in 2.8% of the population in a large single center registry from 2000-2005 ( Table 2 ). ( Doyle et al , 2008 ) Manual compression of the proximal femoral artery and hematoma immediately following discovery and examination should be initiated.…”
Section: Local Vascular Injurymentioning
confidence: 99%
“…In fact, a higher incidence of DVT after femoral catheterization may be possible, but most thrombotic and pulmonary embolic complications are not clinically evident, and their true incidence may be underestimated. 1 In this case, we believe the source of emboli was from the leg vein thrombosis due to excessive compression of the groin and subsequent immobilization. In a previously published clinical trial with a mechanical device pressure dressing, the device was shown to decrease the number of arterial pseudoaneurysms, but was associated with an increased risk of DVTand PE.…”
Section: Discussionmentioning
confidence: 76%
“…PE is rarely reported following coronary angiography [3,4]. The pressure applied to the groin or access site complications such as hematoma or femoral pseudoaneurysm after coronary angiography may cause deep venous thrombosis which may lead to PE [3]. The recommended protocol for patients with massive acute PE or submassive PE with RV dysfunction is 100 mg rt-PA given during a 2-h infusion [5].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided non-surgical treatment is currently Manuscript accepted for publication August 27, 2014 the first-line approach for iatrogenic femoral pseudoaneurysm unless it is too large [2]. Pulmonary embolism (PE) is rarely reported following coronary angiography [3,4]. The pressure applied to the groin or repair of access site complications after coronary angiography may cause PE.…”
Section: Introductionmentioning
confidence: 99%